Evaluation of Erbium Family Lasers’ Effects on Retention of Dental Fiber Post to Resin Cement: Primary Review - Ahmed, Rawaa Abdul Hadi; Basima Mohammed Ali Hussein (Iraqi Journal of Laser, 2024)
Objective: The most common causes of fiber post-failure are inadequate restorations and dislodgement. The fiber post surface’s composition and topography can be altered with laser irradiation which could enhance its retention. This review discusses the effect of the Er:YAG and Er,Cr:YSGG lasers on the surface of fiber posts (FPs) and their strength of adhesion to resin cement in teeth with endodontic therapy. Materials and Methods: A thorough search considering Google Scholar and PubMed, Medline, Scopus, and Web of Science published data from 2013 to 2023 which concentrate on the Erbium family lasers in the fiber post modification to optimize retention and longevity of the coronal restoration in endodontically treated teeth. Results: Twelve studies were recognized and included as reliable sources and reviewed in the study. Data indicated that Surface modification was more effectively achieved with the Er,Cr:YSGG laser than with the Er:YAG laser. In addition to several other evaluation methods, this was primarily accomplished by measuring the pull-out and bush-out shear bonding strength of the fiber post. Conclusion: Er:YAG laser, and Er,Cr:YSGG Laser pre-treatment of FP surfaces were effective in providing high shear bonding strength as a result of surface modification. Bond strength may be reduced and fiber post surfaces may be damaged by high-laser power irradiation.